Marek Sobczyk, Siła wyższa w rzymskim prawie prywatnym, Wydawnictwo TNOiK, Toruń 2005, ss. 331 - Grabowski, Przemysław (Zeszyty Prawnicze, 2017)
Marek Sobczyk, Siła wyższa w rzymskim prawie prywatnym, Wydawnictwo TNOiK, Toruń 2005, ss. 331